RESEARCH OF CONCENTRATED CURD WHEY ELECTROCHEMICAL ACTIVATION PROCESS - Aleksandr Gerasimenko; Aleksey Lodygin; Svetlana Lodygina; Nadezhda Komova; Pavel Nesterenko (Вестник Северо-Кавказского федерального университета)
The topicality of food concentrate on the base of curd whey treated by electrochemical activation method manufacturing is proved. Change in composition and physical-chemical attributes of concentrated curd whey in the course of electrochemical activation is studied.